Development and quality evaluation of high protein and high dietary fibre pasta using lupin flour - Jayasena, Vijay; Nasar-Abbas, Syed (Wiley-Blackwell, 2012)
Pasta samples were prepared by substituting semolina with lupin flour at 0–50% levels. Analysis of the physical properties revealed that cooking loss was not affected by lupin flour incorporation. In dried pasta, the color coordinates L*, a* and b* demonstrated a corresponding increase with lupin flour concentration. However, in cooked pasta, L* and b* values did not show any significant change up to 20% lupin flour incorporation. Lupin flour incorporation resulted in substantial increase in protein and dietary fiber contents. Firmness of freshly extruded pasta decreased at ≥20% lupin flour incorporation. However, firmness of cooked pasta was not affected by lupin flour concentration. Stickiness of cooked pasta decreased at ≥30% lupin flour incorporation. There were no significant changes in color, appearance, taste, texture and overall acceptability up to 20% lupin flour incorporation. It can be concluded that nutritional value of pasta can be improved by lupin flour incorporation without any significant effect on quality.